Construction 4.0 Technologies and Decision-Making: A Systematic Review and Gap Analysis - Hazwani, Shafei; Afiqah, R. Radzi; Algahtany, Mohammed; Rahimi, A. Rahman (MDPI, 2022)
Construction 4.0 involves implementing advanced technologies in construction projects to achieve higher productivity, safety, and sustainability. However, architecture, engineering, and construction (AEC) professionals are reluctant to adopt Construction 4.0 technologies. Lack of information on Construction 4.0 technologies and poor decision-making lead to the issue being unresolved. As a result, the following research question emerged: What are the current trends and research gaps in the existing research on Construction 4.0 technologies and decision-making? This study aims to review the publication trends in Construction 4.0 technologies and decision-making and pinpoint the gaps in prior research. To achieve the aim, a systematic literature review (SLR) was conducted on published articles using the preferred reporting items for systematic review and meta-analyses (PRISMA) method. A total of 22 articles were carefully selected and reviewed. The findings disclosed four research trends: strengths, weaknesses, opportunities, and threats. Also, the findings suggested that existing research still concentrates on adopting and implementing Construction 4.0 technologies. As a result, the existing research has low exploration in integrating Construction 4.0 technologies and decision-making processes. The study findings could guide researchers and AEC professionals to establish effective decisions in achieving Construction 4.0.